2022
DOI: 10.7759/cureus.23387
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Acute Kidney Injury Among Adults Undergoing Cardiac Interventions in King Abdulaziz University Hospital: A Retrospective Review

Abstract: Background Acute kidney injury (AKI) is a syndrome that has been receiving considerable attention as a common risk in cardiac surgeries, which has consequences for short- and long-term survival implications, even for those who do not progress to renal failure. There have been limited studies in the Middle East, and specifically in the Kingdom of Saudi Arabia (KSA). Therefore, our study aimed to identify the prevalence of and risk factors for AKIs following adult cardiac interventions during 2010-202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…In terms of risk factors, the majority of our patients were hypertensive (84.7%), while 336 (72.3%) had diabetes mellitus. This correlates with a research study done by our colleagues in 2022 that showed the most common comorbidity to be HTN 409 (72.5%), followed by DM 392 (69.5%) patients [7].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of risk factors, the majority of our patients were hypertensive (84.7%), while 336 (72.3%) had diabetes mellitus. This correlates with a research study done by our colleagues in 2022 that showed the most common comorbidity to be HTN 409 (72.5%), followed by DM 392 (69.5%) patients [7].…”
Section: Discussionsupporting
confidence: 90%